O-39 Multi-level barriers to advance care planning: Perspectives of healthcare providers, patients and families. (1st September 2015) - Jameson, Kim; Ho, A
Abstract : Background: Advance care planning (ACP) has been shown to support patients in making future healthcare decisions and lower healthcare costs at end-of-life (EOL). Nonetheless, recent studies indicate that communication of ACP and implementation within the Canadian healthcare system remains inadequate. Aim: This presentation discusses healthcare providers' (HCPs), patients' and family members' views towards personal, institutional, and system-level barriers to ACP. Methods: In-depth semi-structured interviews with 83 patients and 41 family members from diverse backgrounds (South Asian, Chinese, Aboriginal, Persian, and Caucasian) and 39 HCPs were conducted in a Western Canadian city. Grounded theory informed the analysis that explored patterns and variations of ACP experiences across and between datasets. Results: Multi-level barriers were reported across all participant groups. Personal barriers centred on relational dynamics (e.g. distrust), communication (e.g. HCPs' own reluctance to engage in EOL discussions), and lack of cultural competence among HCPs. At the institutional level, lack of coordinated care and communication across multi-disciplinary teams hindered the initiation and/or implementation of ACP and a lack of training opportunities for HCPs to engage patients and families of diverse backgrounds in EOL planning. Discussion/conclusion: While all groups reported similar institutional-level barriers, HCPs and patients/families saw the other parties as main contributors of personal-level barriers. Understanding the reasons behind these different perspectives is important. Addressing multi-level barriers through cultivation of HCPs' own EOL communication skills, coordination of care through interdisciplinary team approaches, and cultural competency training, can help HCPs to better support patients of diverse backgrounds and their families in ACP.